intensive course, Cantho 19-29 August 1996 (Cantho, 1996)
The objective of the course is to expose teacher educators with new ideas a materials to develop the skills to implement the new curriculum for the second cycle and to use more inter-active teaching formats.
Keywords: Teaching,Motivation in education,Classroom management,Giáo viên,Hoạt động trong giáo dục